Menakar Implementasi Green Marketing Pada Usaha Kecil Menengah - Dewi Shintawati Kusnadi; Gede Sri Darma (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis research was conducted at Bali Tangi which aims to know, analyze, and interpret from the implementation of green marketing, also to identify the factors that affect the implementation of green marketing. This research was a qualitative descriptive research using phenomenological approach and rationalistic approach. The data process started from reviewing all the data collected from various sources that were interviews, observations already written in field notes, personal documents, official documents, and photographs, resulting in a broad, general and detail analysis.From the research result, it could be concluded that Bali Tangi had commitment of green marketing implementation through “back to nature” concept which used natural and organic ingredients in the manufactured of the products that were in demand to foreign countries. Hopefully, in the future the government can cooperate with Bali Tangi in terms of facilities, infrastructure and even funds to help “Usaha Kecil Menengah” (UKM) or small medium business (SMB) implement green marketing so more SMB can produce environmentally friendly products.